Human immunodeficiency virus type I-specific CD8+ T cell subset abnormalities in chronic infection persist through effective antiretroviral therapy - Gallant Maureen E; Hollett Natasha A; Zipperlen Katrin; Pohling Julia; Grant Michael D (BMC Infectious Diseases, 2010)
Abstract Background Effective highly active antiretroviral therapy (HAART) reduces human immunodeficiency virus (HIV) replication, restores CD4+ T lymphocyte counts and greatly reduces the incidence of opportunistic infections. While this demonstrates improved generalized immune function, rapid rebound to pre-treatment viral replication levels following treatment interruption indicates little improvement in immune control of HIV replication. The extent to which HAART can normalize HIV-specific CD8+ T cell function over time in individuals with chronic infection remains an important unresolved issue. In this study, we evaluated the magnitude, general specificity and character of HIV specific CD8+ T cell responses at four time points across 2-9 years in 2 groups of chronically infected individuals separated on the basis of either effective antiretroviral suppression or ongoing replication of HIV. Methods Peripheral blood mononuclear cells (PBMC) were stimulated with overlapping 15mer peptides spanning HIV Gag, Pol, Env and Nef proteins. Cells producing interferon-γ (IFN-γ) or interleukin-2 (IL-2) were enumerated by ELISPOT and phenotyped by flow cytometry. Results and Conclusions The magnitude of the HIV-specific CD8+ T cell response ranged from < .01 to approximately 1.0% of PBMC and was significantly greater in the group with detectable viral replication. Stronger responses reflected higher numbers of CD8+CD45RA- effector memory cells producing IFN-γ, but not IL-2. Magnitude, general specificity and character of the HIV-specific CD8+ T cell response changed little over the study period. While antiretroviral suppression of HIV in chronic infection reduces HIV-specific CD8+ T cell response magnitude in the short term, it had no significant effect on response character over periods up to 9 years.